2020
DOI: 10.3390/ijms21051876
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles in Zebrafish (Danio rerio) Embryos: Uptake, Growth and Molecular Responses

Abstract: Silver nanoparticles (AgNPs) are widely used in commercial applications as antimicrobial agents, but there have recently been increasing concerns raised about their possible environmental and health impacts. In this study, zebrafish embryos were exposed to two sizes of AgNP, 4 and 10 nm, through a continuous exposure from 4 to 96 h post-fertilisation (hpf), to study their uptake, impact and molecular defense responses. Results showed that zebrafish embryos were significantly impacted by 72 hpf when continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…In contrast, research conducted by Mosselhy and coworkers reported that small (9 nm) PVA-coated silver nanoparticles caused a more significant mortality rate and higher delay in the hatching rate in comparison with bigger PVA-capped NPs (30 nm) [105]. This is in agreement with recent work on two sizes (4 and 10 nm) of Ag-NPs [104]. Exposed larvae to the 4 nm Ag-NPs exhibited delayed yolk sac absorption and decreased body length, while those treated with 10 nm Ag-NPs did not present these perturbations.…”
Section: Influence Of Silver Nanoparticle Size On Toxicitysupporting
confidence: 89%
“…In contrast, research conducted by Mosselhy and coworkers reported that small (9 nm) PVA-coated silver nanoparticles caused a more significant mortality rate and higher delay in the hatching rate in comparison with bigger PVA-capped NPs (30 nm) [105]. This is in agreement with recent work on two sizes (4 and 10 nm) of Ag-NPs [104]. Exposed larvae to the 4 nm Ag-NPs exhibited delayed yolk sac absorption and decreased body length, while those treated with 10 nm Ag-NPs did not present these perturbations.…”
Section: Influence Of Silver Nanoparticle Size On Toxicitysupporting
confidence: 89%
“…It has been suggested that there might be an optimal particle size for active uptake; for example, in human cell lines exposed to different AgNPs sizes, the 50 and 100 nm had higher uptake efficiencies compared to the smaller size (20 nm) [49,50]. Similarly, Qiang et al, 2020 suggested the smaller sizes up to 20 nm are more likely to be internalised than larger sizes, providing evidence for enhanced uptake and toxicity for smaller sizes (4 nm) in zebrafish embryos [51]. Another study demonstrated that the uptake efficiency of 5 and 100 nm AgNPs after 24 h was higher (58 and 63% respectively) compared to other sizes (20 nm and 50 nm) [49], supporting our findings.…”
Section: Discussionmentioning
confidence: 99%
“…50 It is known that the presence of proteins and salts and in cell medium can either reduce or enhance the toxicity of NPs as well as inducing alterations in the physiochemical characteristics of the NPs, such as changes in the size, shape, and surface area. 18,[51][52][53] In this regard, the characterisation in CCM and SFM by DLS demonstrated that the serum had a stabilizing effect on the NPs, as the hydrodynamic size did not change over 24 hours, compared to the AgNPs in SFM, which revealed major agglomeration after 24 hours. Moreover, the zeta potential in CCM treatments remained similar at both time points suggesting that corona formation around the PVP-capped AgNPs in CCM provided additional stability, with corona formation also evidenced by the slight increase in size as a result of the binding of serum proteins onto the NPs' surface.…”
Section: Discussionmentioning
confidence: 93%